Tax-related and Economic Consequences of Selecting the Method of Debt Financing of Companies with Regard to Thin Capitalisation in OECD Member Countries - Dominik Gajewski (Contemporary Economics)
The following paper explores the issue of thin capitalisation in Organisation for Economic Co-operation and Development (OECD) member countries. There are two methods used by financing companies that are strongly related to this phenomenon: debt and equity financing. The tax-related consequences arising from choosing the debt financing method in companies with regard to thin capitalisation are analysed in this paper. It is argued that it is the tax policy of a company that directly influences the economic consequences of its operation. The taxation of thin capitalisation may be carried out in various forms depending on the adopted method. The tax-related implications point to the complexity of this process regardless of the country in which it takes place. However, the problem becomes even more complicated in the case of taxation of this process in companies undertaking cross-border activity.